METABOLIC SYNDROME IN SCHOOL CHILDREN OF DERA ISMAIL KHAN, PAKISTAN - Ramzan, Muhammad; Ali, Irshad; Ramzan, Faiqah; Ramzan, Faiza; Ramzan, Muhammad Haris (Journal of Ayub Medical College Abbottabad, 2010)
Background: Childhood obesity has increased considerably in many regions of the world including Pakistan. The recent phenomenon of '˜nutritional transition' with a westernisation of food so prevalent in developing countries, has caused a significant rise in obesity among population that were unaware of this problem in the recent past. The aim of this study was to find out the frequency of metabolic syndrome and cardiovascular risk factors in obese school children (6-11 years) in Dera Ismail Khan. Methods: Eighty-six children were included in this study with 61 (70.94%) obese and 25 (29.06%) normal weight children. Obese children comprised of 34 (39.53%) boys and 27 (31.40%) girls. Normal weight children included 15 (17.44%) boys and 10 (11.63%) girls. They were selected among 1,336 children from 8 primary schools of Dera Ismail Khan city. Anthropometric parameters of each subject were recorded, BMI determined and body mass status calculated. Children were categorized by the presence or absence of Obesity. Blood Pressure was also measured. Non-fasting venous blood samples were taken, analysed for lipids; Triglycerides (TG), Cholesterol (TC); Lipoproteins: High and Low Density Lipoprotein-cholesterol (HDL-C, LDL-C) and Plasma Glucose Concentration (PGC). Metabolic syndrome was identified in the presence of ‰¥3 of the followings with cut-off values: TG>170 mg/dl, HDL-C<35 mg/dl, WC>71 cm, BP >120/80 mm Hg, PGC>200 mg/dl. Results: Metabolic syndrome was identified in 22.95% of the obese children. It was 19.67% and 3.27% in obese boys and girls respectively. Metabolic syndrome was not found in normal weight children. Clustering of cardiovascular factors was abundantly present in obese and rare in normal weight children. Keywords: Metabolic Syndrome, Cardiovascular Risk Factors, Obese School Children, Lipid Profile